P3.62 Adult prevalence of active syphilis in low- and middle-income countries, 1995–2016: baseline and prospect for reductions targeted through the global sti control strategy 2016–2021. (8th July 2017) - Korenromp, Eline; Mahiané, Guy; Nagelkerke, Nico; Rowley, Jane; Pretorius, Carel; Kassebaum, Nicholas; Taylor, Melanie; Abu-Raddad, Laith
Abstract : Introduction: The World Health Organisation and many countries have set targets to reduce rates of syphilis and eliminate congenital syphilis. National trends in syphilis prevalence and incidence, however, are uncertain. We used the Spectrum-STI model to estimate prevalence trends of active syphilis in adult women, for countries with ≥3 data points post-1999 including ≥1 from year 2009 or later. Methods: Prevalence data were adjusted for diagnostic test performance, and for the contribution of high-risk populations under-represented in surveys. National trends were estimated by logistic regression, weighting each data point by its national coverage. Estimates for 117 countries were aggregated to regional totals, weighting each country by adult population size, and imputing for countries without a trend estimate using regional averages. Results: At January 2017, 1056 data points had been identified, between 1977–2016 (median 2009), covering 137 million tests (132 million in routine ANC screening, 5.3 million in ANC surveys; 0.79 million from non-ANC general adult population surveys), of which 1.36 million found active infection. In provisional estimates, prevalence was highest in sub-Saharan Africa and lowest in Europe and the Middle East and North Africa (MENA). Prevalence declined over 2002–2012 in all regions, with strongest proportional decline in MENA (≥1% to<0.1%) and largest absolute decline in Africa (≥3% to 1%–1.8%). Trends over 2012–2016 remain to be confirmed with new data, including general population HIV and syphilis surveys conducted over 2015–2018 in some African countries. Conclusion: Spectrum-STI is a useful tool to interpret syphilis data in a systematic manner, and evaluate time trends in national adult syphilis prevalence; however some high-STI countries lack recent data from ANC or any other general populations. These first standardised country estimates suggests that syphilis declines need to accelerate in most countries, if by 2021 they are to meet impact targets of the global STI control strategy and eliminate congenital syphilis.